The potential of individual factor towards graduate on time (GOT) among PHD students in University Utara Malaysia (UUM) - Nor Farah Ain, Mohamed Azman (2020)
One major issued faced by higher learning institutions in many countries’ especially Malaysia is Graduate on Time (GOT), particularly among PhD students. This is followed by the concerns of university images and rankings. Past studies have shown that Graduate on Time (GOT) could be influenced by various factors. Therefore, this study investigated the relationship of individual factors such as personality type A and B, motivation, knowledge, skills, and abilities, and knowledge sharing behavior as a predictor of graduate on time. A total of four hypotheses were developed, and binary logistic regression was carried out to examine the effect. The sample consisted of 159 PhD students and students were selected starting from 3rd semester and above. This is because the outcome of graduation among 1st-semester students is not identifiable. Two of the hypotheses were supported, and the results showed that knowledge, skills, and abilities and knowledge sharing behavior have a significant effect on the outcome of graduate on time. This study aims to implement the proposed models that comprise several factors in predicting the outcome of students that will complete their PhD studies on the predetermined time. The analysis techniques used are Binary Logistic Regression Model, whereby a set of data were examined to determine the outcome. The results and findings in this study may contribute major insights into institutions and students themselves as the gaps concerning student’s personality traits as the causes of the decrease of graduation rates and how to handle and measure them. Moreover, the findings also imply that personality types seem to be a new predictor in research which lead to a person actions that may influence their completion of studies. Thus, stakeholders should join hands in providing a better solution to sustain the credibility of students and institutions as a whole.